Electrolyte Imbalance in Elderly Stroke Patients: A Retrospective Analysis from a Tertiary Center - Raeba Eldhose; K. G. Gopinath; Jini Chirackel Thomas (Journal of the Indian Academy of Geriatrics, 2025)
Background and Aim: The morbidity and mortality associated with stroke in older persons are high, and electrolyte imbalances may play an important role. Early detection and correction of these factors can improve patient outcomes. This study aimed to assess electrolyte imbalance in patients presenting to a tertiary care center with acute stroke. Materials and Methods: This was a retrospective observational study conducted in the department of geriatrics of a tertiary care hospital in South India. We included 43 inpatients aged ≥60 years who were admitted with an acute stroke between November 2019 and November 2021. Laboratory values of sodium, potassium, calcium, and phosphorus checked during the inpatient stay were recorded. Data were obtained from the discharge summaries, electronic medical records, and online prescriptions. Results: Forty-three patients were included in the study, of which 33 (77%) had ischemic stroke (IS) and 10 (23%) had hemorrhagic stroke. Electrolyte imbalance was observed in 27 (62.8%) patients. Eighty percent of hemorrhagic stroke patients and 57.7% of IS patients had an electrolyte imbalance. The most common electrolyte imbalance was hyponatremia (25.5%), followed by hypokalemia (20.9%). Fourteen percent had hypophosphatemia, 9.3% had hyperphosphatemia, 4% had hyperkalemia, 4.7% had hypernatremia, and 2.3% had hypocalcemia. Conclusion: Electrolyte imbalance is common in patients presenting with acute stroke. Hyponatremia is the most common electrolyte abnormality, followed by hypokalemia. Patients with an acute stroke should be regularly assessed for electrolyte abnormalities.